2015
DOI: 10.1016/j.watres.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Anatoxin-a producing Tychonema (Cyanobacteria) in European waterbodies

Abstract: Keywords:Anatoxin a Tychonema Cell quotaPolyphasic approach Phylogenetic analysis European waterbodies a b s t r a c tIn order to identify the cyanobacterial species responsible of anatoxin a (ATX) production in Lake Garda (Northern Italy), an intensive isolation and culturing of filamentous cyano bacteria were established since 2014 from environmental samples. In this work, we report a detailed account of the strategy adopted, which led to the discovery of a new unexpected producer of ATX, Tychonema bourrelly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…This was not unexpected, considered that recent investigations had already shown that the populations isolated in the Italian district do not have the capability to produce ATX. T. bourrellyi was found to produce ATX, as reported also in recent papers Shams et al, 2015). Moreover, based on evidences collected in this work, this species was possibly able to synthesize PSP toxins, possibly sulfated variants (like C3/4 toxins).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was not unexpected, considered that recent investigations had already shown that the populations isolated in the Italian district do not have the capability to produce ATX. T. bourrellyi was found to produce ATX, as reported also in recent papers Shams et al, 2015). Moreover, based on evidences collected in this work, this species was possibly able to synthesize PSP toxins, possibly sulfated variants (like C3/4 toxins).…”
Section: Discussionsupporting
confidence: 84%
“…In particular, based on the analysis of isolated strains (Bernard et al, 2016), Aph. flos-aquae and T. bourrellyi were reported as ATX producers (Sivonen et al, 1989;Osswald et al, 2009;Salmaso et al, 2015;2016;Shams et al, 2015), whereas M. aeruginosa and P. rubescens were mainly reported as MC producers (Metcalf and Codd, 2012), and D. lemmermannii as MCs and anatoxin-a(S) producer (Sivonen et al, 1992;Onodera et al, 1997). Our targeted analysis confirmed this behavior for M. aeruginosa and P. rubescens, but not for Aph.…”
Section: Discussionsupporting
confidence: 54%
“…The species did not show differences in cell dimension at the different depths along the water column, but seasonal variations were observed. In April, P. rubescens considerably increased in biovolume compared to T. bourrellyi, as its cells displayed the highest diameter (6.33 µm), with a cell volume of 150 µm 3 . The average annual cell volume of P. rubescens and T. bourrellyi had the same value (63 ± 4 and 63 ± 2 µm 3 respectively), with a mean annual diameter of 4.38 ± 0.11 and 4.2 ± 0.08 µm, and a mean annual length of 3.95 ± 0.04 and 4.50 ± 0.08 µm, respectively.…”
Section: Seasonal and Spatial Dynamics Of P Rubescens And T Bourrellyimentioning
confidence: 99%
“…As a result of their long evolutionary history (~2 by) [1,2], and due to their high ecological plasticity, Cyanobacteria are able to adapt to geochemical and climatic changes [3,4]. Consequently, these organisms are also capable of adapting to anthropogenic modifications of aquatic environments [5], such as enhanced nutrient loading or increasing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria produce a wide range of toxic compounds, including neurotoxins and hepatotoxins, which can have adverse effects on environmental and public health (Sivonen, 1996). Anatoxin-a (ATX-a), one of the main neurocyanotoxins produced by several genera of cyanobacteria, including Anabaena, Aphanizomenon, Oscillatoria, Cylindrospermum, Planktothrix, Phormidium and Tychonema, was first identified from an Anabaena flos-aquae strain in the 1970s (Osswald et al, 2007;Shams et al, 2015;Devlin et al, 1977). It exhibits extreme toxicity, killing mice within 2-5 min, and was initially known as ''very fast death factor'' (Devlin et al, 1977).…”
Section: Introductionmentioning
confidence: 99%